2022
DOI: 10.52236/ih.v10i2.250
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Senam Qigong Terhadap Tingakat Kecemasan Lansia Di BPSTW Unit Budi Luhur Yogyakarta

Abstract: Kecemasan pada lansia berhubungan erat dengan kondisi fisik dan psikologis akibat proses penuaan dan penyakit neuro-degeneratif. Kecemasan yang berkepanjangan memperburuk keadaan lansia yang berakibat pada komplikasi berbagai macam penyakit dan menurunnya kualitas hidup lansia. Alternatif intervensi keperawatan nonpharmakologis yang aman dan efektif diperlukan untuk dapat diimplementasikan kepada lansia yang mengalami kecemasan, salah satunya adalah senam qigong. Tujuan penelitian diketahuinya efektifitas sena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The of Yogjakarta, the results obtained were ρvalue = 0.000 (ρv < 0.05) for systolic blood pressure and ρ -value = 0.028 (< 0.05) for diastolic blood pressure. In this study, it was concluded that there was an effect of meditation therapy on changes in systolic and diastolic blood pressure in the elderly (Asmarani, 2018). The relaxation stages in meditation in the form of regulating deep breathing and calming yourself, controlling your thoughts or focusing your mind so you can feel relaxed within 15 minutes, can make the sympathetic nerves in the brain reduce emotional stimulation (Peper, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The of Yogjakarta, the results obtained were ρvalue = 0.000 (ρv < 0.05) for systolic blood pressure and ρ -value = 0.028 (< 0.05) for diastolic blood pressure. In this study, it was concluded that there was an effect of meditation therapy on changes in systolic and diastolic blood pressure in the elderly (Asmarani, 2018). The relaxation stages in meditation in the form of regulating deep breathing and calming yourself, controlling your thoughts or focusing your mind so you can feel relaxed within 15 minutes, can make the sympathetic nerves in the brain reduce emotional stimulation (Peper, 2019).…”
Section: Discussionmentioning
confidence: 91%